2001
DOI: 10.1002/etc.5620200425
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence as a bioindicator of effects on growth in aquatic macrophytes from mixtures of polycyclic aromatic hydrocarbons

Abstract: Abstract-Chlorophyll-a fluorescence induction is a rapid technique for measuring photosynthetic electron transport in plants. To assess chlorophyll-a fluorescence as a bioindicator of effects of polycyclic aromatic hydrocarbon mixtures, chlorophyll-a fluorescence parameters and plant growth responses to exposure to the wood preservative creosote were examined in the aquatic plants Lemna gibba and Myriophyllum spicatum. Exposure to creosote inhibited growth of L. gibba (EC50 ϭ 7.2 mg/L total polycyclic aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 45 publications
(69 reference statements)
8
86
0
1
Order By: Relevance
“…Among the parameters used to describe fluorescence of chl, initial fluorescence of Chl (F 0 ), potential yield of photochemical reactions in PSII (F v /F m ), and effective quantum yield of PSII (ϕ PSII ) are used most frequently in studying the stress physiology of plants (Krause and Weis, 1991;Marwood et al, 2001;Mallick and Mohn, 2003;Kummerová and Vanová, 2007). In the present study, F 0 was greater when soybeans were exposed to Cd or FLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the parameters used to describe fluorescence of chl, initial fluorescence of Chl (F 0 ), potential yield of photochemical reactions in PSII (F v /F m ), and effective quantum yield of PSII (ϕ PSII ) are used most frequently in studying the stress physiology of plants (Krause and Weis, 1991;Marwood et al, 2001;Mallick and Mohn, 2003;Kummerová and Vanová, 2007). In the present study, F 0 was greater when soybeans were exposed to Cd or FLT.…”
Section: Discussionmentioning
confidence: 99%
“…Because PSII is the first step in photosynthetic electron transport, inhibition of electron transport anywhere within the electron transport chain exerts excitation pressure on PSII. Changes in PSII and ϕ PSII indicate a greater proportion of inactive PSII reaction centers due to inhibition of photochemical processes of photosynthesis related to electron transport chain in the thylakoid membrane, such as oxidation or degradation of D1 proteins, impairment of PSI leading block of the downstream electron transport, and severely reduced pigment concentrations in reaction centers (Anderson et al, 1997;Huang et al, 1997;Marwood et al, 2001). The results of the current study indicated that exposure to Cd or FLT resulted in less absorption of light energy, electron transport, conversion of light energy and photo phosphorylation in soybean seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The principles of this method are described in [38][39][40]. The quantum yield of the PSII correlates with photosynthetic carbon assimilation [38] and indicates inhibition of photosynthetic activity by a stressor [41,42]. For these measurements, the test organisms had to be taken off the medium.…”
Section: Measurements Of the Quantum Yieldmentioning
confidence: 99%
“…In plants, they cause oxidative stress with a high level of generation of Reactive Oxygen Species (ROS), cell death, and necrosis (Burritt, 2008;Paskova et al, 2006). They affect growth by reducing photosynthesis activity, transpiration rate, and nutrient uptake (Liu et al, 2009;Marwood et al, 2001;Redondo-Gómez et al, 2011;Witting et al, 2003).…”
Section: Introductionmentioning
confidence: 99%